Географічне поширення Iris sibirica L. в Україні - Podorozhniy, D.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The current distribution of rare species Iris sibirica L. was established in Ukraine. A range of I. sibirica distribution are lined. All I. sibirica known localities are listed and mapped.